Christianity and the notion of nothingness : contributions to Buddhist-Christian dialogue from the Kyoto school - Mutō, Kazuo, 1913-1995 (Philosophy of religion. World religions, 2012)
The Christian philosopher Muto Kazuo contributed substantially to the predominantly Buddhist "Kyoto School of Philosophy." Through critical exchange with its representatives, he opened up new perceptions of Christian faith, enabled mutual understanding between Buddhism and Christianity, and challenged the Western dialectical method.